Why Students Choose Social Work? - Akbar Prayuda; Fadhil Nurdin (Asian Social Work Journal, 2018)
University and college that organize the education of social workers and social welfare, give a chance for Indonesia to produce professional practitioners in social worker sector to be much better. The students of social work education hoped having ability about professional helping process, so that can help an individual, family, group and society to solve the social problem. This picture define that social work has a great future for develop our nation, so important to produce a prosperity social worker. The problem is, profession of social worker had not recognized by society, many people did not know what social work is. Grounded on this fact, it interest to find out why candidate student make a choice to study in social work or social welfare, whereas they don’t know about social worker profession. This research purposed to knowing why student of social work have been made a future decision to continue study in Social Work Scholar. This qualitative research use case study approach was success collecting information from six informants in four different universities in Bandung and Makassar by pursposive- snowball. Six informant clarified that they have continue study to social work by some reason, (1) obey their parents and family, (2) They need to work for government (ASN) after graduated, (3) in a pinch because of particular situation. Recommendation of this study emphasizes on give attention to social work and social welfare education system, optimize social work existence in public and encourage government to legitimating social work act in Indonesia.